Known Posters, Unknown Impact. OSPAAAL Graphic Art and Its Worldwide Reception - Ayo Schmiedecke, Natália (Jahrbuch für Geschichte Lateinamerikas, 2025)
In recent years, the literature on the Cold War era has given increasing attention to the so-called Third World project and has proposed new concepts to analyze its different currents, such as Tricontinentalism. Scholars agree that the propaganda materials produced by the Cuba-based Organization of Solidarity with the Peoples of Africa, Asia and Latin America (OSPAAAL, 1966-2019) played a crucial role in disseminating the Tricontinentalist agenda, vocabulary and imagery. But this general agreement is not anchored in empirical evidence, since the circulation and reception of these materials have been understudied so far. This paper argues that debates on Tricontinentalism have much to gain from expanding this front. By focusing on the OSPAAAL posters, I will explore four avenues – their distribution; reproductions and versions; iconographic and stylistic influence; and presence in books, exhibitions and archives – highlighting the methodological difficulties involved in this endeavor. The paper organizes data obtained from archival documents, works by other scholars and interviews published in different parts of the world. This approach challenges generalizations based on very specific primary sources, as well as theorizations not grounded in rigorous empirical analysis. This study reaffirms the importance of a Cold War history that considers the particular dynamics of the so-called Third World, their global connections, as well as the visual dimension of the antagonisms and solidarities built in that context. At the same time, it emphasizes the importance of a long-term perspective when looking into the global sixties.
Keywords: Tricontinentalism; Cuban Poster Art; Visual Culture.